THE FENOMENON OF HUMAN TRAFFICKING IN MOZAMBICAN LEGAL SYSTEM (ESMAT Magazine, 2024)
This theme aims to focus on the phenomenon of human trafficking in the Mozambican legal system. The crime of human trafficking culminates in the violation of people's rights and freedoms, as well as the violation of human dignity. Due to the social and economic weaknesses that the State faces, such as extreme poverty, unemployment and the poor performance of regulations, many people become easy targets for traffickers. Therefore, the general objective of this work is to analyze human trafficking in Mozambique and from this the specific objectives of analyzing the legal treatment of the crime of human trafficking in the Mozambican legal system and prevention mechanisms unfold. Strictly speaking, bibliographic research and documentary research are used to provide a theoretical and legal basis for the work and, regarding the method, we opted to use the deductive method that served as a guide in preparing the work. In the end, the conclusion was reached that public policies implemented by the State are necessary to protect the human person.
Keywords: Human Trafficking. Exploitation. Rights and Freedoms. Human Dignity.